2020
DOI: 10.1111/1759-7714.13526
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow prognostic score predicts efficacy and prognosis in patients with advanced non‐small cell lung cancer receiving EGFR‐TKI treatment

Abstract: Background Lung cancer is the leading cause of cancer‐related deaths. Although epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) are effective for advanced non‐small cell lung cancer (NSCLC) harboring EGFR mutations, some patients experience little or no response. The Glasgow prognostic score (GPS) is an inflammation‐related score based on C‐reactive protein (CRP) and albumin concentrations, and has prognostic value in various cancer settings. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Table 4 summarizes the studies till date that have evaluated the GPS in patients administered anticancer drug therapy for advanced NSCLC. All reports on studies using cytotoxic anticancer drugs, molecularly targeted drugs, and ICIs have indicated the usefulness of the GPS 5,6,13,14,36‐40 . However, although certain reports have incorporated first‐line pembrolizumab monotherapy, no reports have focused on first‐line pembrolizumab monotherapy in patients with high PD‐L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 summarizes the studies till date that have evaluated the GPS in patients administered anticancer drug therapy for advanced NSCLC. All reports on studies using cytotoxic anticancer drugs, molecularly targeted drugs, and ICIs have indicated the usefulness of the GPS 5,6,13,14,36‐40 . However, although certain reports have incorporated first‐line pembrolizumab monotherapy, no reports have focused on first‐line pembrolizumab monotherapy in patients with high PD‐L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…GPS is a proven systemic inflammatory response‐based scoring system, measuring serum CRP and Alb levels 19,20 . It is a reliable prognostic indicator for patients with various forms of cancer including lung cancer 19–23 . There have also been reports showing an association between GPS and chemotherapy‐related adverse events 24,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, patients with ILD, NSCLC, and a GPS score of 0 might have a better OS and benefit from a more aggressive chemotherapy regimen because of a lower risk for AE‐ILD. Furthermore, we calculated the GPS from blood test results before the onset of first‐line chemotherapy, according to the existing reports 21–24 . However, the GPS may change upon treatment or tumor activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 After its introduction, GPS was reported to be a reproducible predictor of long-term prognosis for NSCLC and SCLC. [29][30][31][32][33][34][35][36][37][38] However, there have been no previous studies examining the relationship between GPS and SCLC with concomitant ILD in patients undergoing chemotherapy. Therefore, the purpose of this study was to determine whether GPS predicts prognosis and chemotherapy-triggered AE-ILD in patients with SCLC and concomitant ILD.…”
Section: Introductionmentioning
confidence: 99%